Exploring Chinese Students’ Learning Experiences in a Private Higher Education Institution in the Philippines towards a Proposed Global Engagement Initiative Program - Peng, Shao (JPAIR Multidisciplinary Research, 2024)
n response to the growing number of foreign students in the Philippines, Philippine higher education institutions have begun offering competitive programs to establish a global presence and foster internationalization. This study explored the educational experiences of Chinese graduate students at St. Paul University Manila. Through a qualitative research approach, the study explored Chinese students’ motivation for participating in an international program in a private higher education institution, expectations and their significant learning experiences as an international student, goal achievements in the international program, and their advice and recommendations for future international higher education students. Using a phenomenological research method incorporating open-ended questionnaires, the study analyzed narratives and reflections from the participants to understand their academic, cultural, and personal adaptation processes. The findings underscore key motivators, including career advancement, cultural exchange, and the institution’s reputation. Themes reveal that students highly value the quality of education, multicultural interactions, and the opportunity to improve their English communication skills. These findings served as a basis for proposing a “Global Engagement Initiative” Program to enrich international students’ experiences through tailored support services and intercultural programs. This initiative is envisioned to address students’ academic needs and foster their integration and satisfaction, enhancing St. Paul University’s and other private universities’ global appeal and support for international education.